Vocal nodules management. (26th April 2019) - Birchall, Martin A.; Carding, Paul
Abstract : Vocal fold nodules present the voice clinic team with a number of clinical dilemmas which are not as simple as previously thought. The definition, aetiology, prevalence and diagnosis are all poorly understood. Furthermore, treatment evidence for both behavioural and surgical approaches is weak. This paper reviews the published evidence pertaining to all of these aspects. Specific areas of uncertainty that remain include poorly defined nomenclature, the natural history of paediatric vocal nodules, the establishment of criteria to measure successful treatment, optimal configuration of speech therapy regimens and the rationale for surgical intervention. The authors suggest the development of evidence‐based guidelines for UK practice.